2009
DOI: 10.1152/japplphysiol.91289.2008
|View full text |Cite
|
Sign up to set email alerts
|

Skin blood flow and nitric oxide during body heating in type 2 diabetes mellitus

Abstract: Individuals with type 2 diabetes mellitus (T2DM) often exhibit microvascular dysfunction that may contribute to impaired thermoregulation, but potential mechanisms remain unclear. Our goals were to quantify skin blood flow responses and nitric oxide-mediated vasodilation during body heating in individuals with T2DM compared with nondiabetic control subjects of similar age. We measured skin blood flow (laser-Doppler flowmetry) in conjunction with intradermal microdialysis of N(G)-nitro-l-arginine methyl ester (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
46
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 18 publications
4
46
1
Order By: Relevance
“…We previously reported that cutaneous vasodilation during whole body heating exhibited a delayed onset in T2DM subjects (14) and that overall vasodilator responses were lower at a given core temperature in T2DM compared with control subjects of similar age and body size (13). Additionally, we found that the prolonged local warming response (nitric oxidedependent "plateau phase" vasodilation) was decreased in T2DM subjects (12,14).…”
Section: Discussionmentioning
confidence: 57%
See 4 more Smart Citations
“…We previously reported that cutaneous vasodilation during whole body heating exhibited a delayed onset in T2DM subjects (14) and that overall vasodilator responses were lower at a given core temperature in T2DM compared with control subjects of similar age and body size (13). Additionally, we found that the prolonged local warming response (nitric oxidedependent "plateau phase" vasodilation) was decreased in T2DM subjects (12,14).…”
Section: Discussionmentioning
confidence: 57%
“…Blood glucose was measured in all T2DM subjects before any procedures began. Two intradermal microdialysis fibers (MD-2000; Bioanalytical Systems) were placed in the skin on the ventral surface of the left forearm of each subject, as previously described (12,13). Ice was placed on the skin surface for 2-3 min to numb the area.…”
Section: Study Visitmentioning
confidence: 99%
See 3 more Smart Citations